Association between serum ca-125 levels and severity of pre-eclampsia: a case-control study conducted in a tertiary care centre, West Bengal - Mukherjee, Bijoya; Das, Amiya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Screening test for pre-eclampsia has been a topic of extensive research in last few decades, and to identify a cost effective and accurate one is of immense importance. This study was conducted to determine an association between serum CA-125 levels and severity of pre-eclampsia, and thus to specify clinical utility of this biochemical marker in prediction, diagnosis and follow-up of pre-eclampsia. Methods: A case-control study involving 40 women with non-severe pre-eclampsia, 40 women with severe pre-eclampsia and 40 healthy pregnant women matched for age, parity and gestational age at enrolment were taken in a tertiary care centre in West Bengal. Results: The CA-125 levels in three categories of participants were: normotensive (15.76±2.95), non-severe pre-eclampsia (26.98±2.28), severe pre-eclampsia (44.99±11.23), p<0.001. CA-125 levels correlated positively with systolic blood pressure (r=0.78, p<0.001), diastolic blood pressure (r=0.79, p<0.001), negatively with platelet levels (r=-0.67, p<0.001) and with birth weight of baby (r=-0.54, p<0.001). When cut-off for serum CA-125 levels was accepted as 35 IU/ml, the sensitivity and specificity of the marker was found to be 92.1% and 97.1% respectively. Positive predictive value 95.5%, Negative predictive value 94.4%. Conclusions: We can infer from this study that maternal serum CA-125 levels are associated with pre-eclampsia and its severity. As it is much more available and less expensive, it seems to be a promising as a screening test.